1991
DOI: 10.1200/jco.1991.9.11.1945
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous recombinant interferon beta in patients with recurrent malignant gliomas: a phase I/II study.

Abstract: A multicenter phase I/II trial of a human recombinant interferon beta (Betaseron; Triton Biosciences, Alameda, CA) was conducted in patients with recurrent glioblastoma and anaplastic astrocytoma in six centers between 1986 and 1988. Betaseron was given intravenously three times per week, starting at 90 x 10(6) IU per dose and escalating by 90 x 10(6) IU every 2 weeks up to a maximum dose of 540 x 10(6) per treatment. All patients had failed prior radiotherapy, and most had failed one or more courses of chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…IFN-h is a particularly good choice to show the proof of principle of this approach because phase I clinical trials of recombinant human IFN-h have shown that although responses do occur, systemic delivery of high doses of IFN-h is associated with toxicity and a narrow therapeutic index that limits the overall efficacy (48)(49)(50)(51)(52). Because IFN-h functions physiologically as a paracrine factor, its antitumoral effects can be enhanced and its toxicity is reduced if it is given locally (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-h is a particularly good choice to show the proof of principle of this approach because phase I clinical trials of recombinant human IFN-h have shown that although responses do occur, systemic delivery of high doses of IFN-h is associated with toxicity and a narrow therapeutic index that limits the overall efficacy (48)(49)(50)(51)(52). Because IFN-h functions physiologically as a paracrine factor, its antitumoral effects can be enhanced and its toxicity is reduced if it is given locally (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…radiation or other chemotherapeutic drugs (9,(31)(32)(33). IFN-ß has also been used for patients with solid tumors including malignant gliomas with only marginal benefit; a therapeutic guideline for optimal clinical efficacy has not been determined (23,34). It has been reported that the antitumor effect of IFN-ß can be improved through the combination with chemotherapy and radiation therapy (26).…”
Section: Suppression Of U-87 Cell Migration By Tmz and Ifn-ß Combinatmentioning
confidence: 99%
“…Also, several in vitro and in vivo studies (16)(17)(18)(19) have demonstrated an antiangiogenic activity attributed to IFN-ß in tumors. Chronic systemic administration of IFN-· or IFN-ß has been observed to produce regression of vascular tumors including Kaposi sarcoma (20), pulmonary hemangiomatosis (21), and hemangiomas (22); with only a marginal benefit for malignant gliomas (23). It has been reported that the combination of IFN with chemotherapy drugs increases the antitumor effects (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…The first biologic immunomodulatory treatment used in the management of glioblastoma was interferon (IFN). Several clinical trials of IFN either alone or in combination with cytotoxic chemotherapy have been conducted, but treatment is associated REviEW Domingo-Musibay & Galanis future science group with significant side effects related to therapy, including fatigue and flu-like symptoms, without convincing evidence of efficacy [41][42][43].…”
Section: Immunotherapeutic Approachesmentioning
confidence: 99%